2013
DOI: 10.1128/jvi.01657-13
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Cellular Distribution of Human Cytomegalovirus Helicase by Cellular Factor Snapin

Abstract: bControlled regulation of genomic DNA synthesis is a universally conserved process for all herpesviruses, including human cytomegalovirus (HCMV), and plays a key role in viral pathogenesis, such as persistent infections. HCMV UL105 is believed to encode the helicase of the DNA replication machinery that needs to localize in the nuclei, the site of viral DNA synthesis. No host factors that interact with UL105 have been identified. In this study, we show that UL105 specifically interacts with Snapin, a human pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Zhou et al (30), have revealed that Snapin has a critical role in coordinating dynein-driven retrograde transport and late endosomal-lysosomal trafficking, thus maintaining efficient autophagy-lysosomal function. In addition, a number of studies have demonstrated that Snapin may regulate HCMV genomic DNA synthesis by modulating the cellular distribution of viral helicase (25,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (30), have revealed that Snapin has a critical role in coordinating dynein-driven retrograde transport and late endosomal-lysosomal trafficking, thus maintaining efficient autophagy-lysosomal function. In addition, a number of studies have demonstrated that Snapin may regulate HCMV genomic DNA synthesis by modulating the cellular distribution of viral helicase (25,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…As a novel HCMV encoded major histocompatibility complex (MHC) class I-related molecule, the UL142 protein contains an MHC class I Antigen (MICA) recognition domain (17,18), which is able to downregulate the expression levels of the NKG2D ligand, leading to protection from NK cytotoxicity and inhibition of NK cell-mediated lysis (19)(20)(21)(22). Snapin, expressed in a number of types of cells, including adipocytes and neuronal cells (23)(24)(25)(26), has been established to be associated with the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex (27,28). SNAREs are ubiquitous proteins that direct vesicular trafficking and exocytosis, and mediate the release of neurotransmitters in neurons (29).…”
Section: Discussionmentioning
confidence: 99%
“…Human foreskin fibroblasts (HFF cells, passages 9 to 14), Human astrocytoma U251 cells (U251 cells), and Human Embryonic Kidney 293 cells (293 cells) were maintained in Dulbecco’s modified Eagle medium (DMEM), containing 10% fetal bovine serum, as previously described [ 19 , 20 ]. Herpes simplex virus 1 (HSV-1) was provided by Fenyong Liu (University of California, Berkeley, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Viral DNA was extracted from mock or HCMV-infected cells using a DNeasy tissue kit (Qiagen, Hilden, Germany). Intracellular viral DNAs were quantified using primers and a probe for amplifying the HCMV UL83 DNA region, as previously described [ 19 ]. The reaction was performed in a 20-μL amplification mixture (2 μL of DNA extract, 10 μL of 2 × Premix Ex Taq TM (TaKaRa, Dalian, China), 0.4 μL each of primer at 10 μM, 0.8 μL of the fluorogenic probe at 5 μM, 0.4 μL 50 × ROX Reference Dye II) using an ABI 7500 device (Applied Biosystems Inc., Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation